Kontrol Optimal pada Model Penyebaran SARS-CoV-2 dengan Pelaksanaan Testing dan Perawatan - Aliza Dame Rohana Sianipar; Lasker Pangarapan Sinaga (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
COVID-19 (Corona Virus Disease 2019) is a disease of the respiratory system caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The COVID-19 pandemic was declared active by WHO in March 2020 and the pandemic status was lifted on May 5, 2023. COVID-19 must still be watched out to prevent a new wave of pandemics, so an optimal control analysis is needed. The purpose of this study is to determine the optimal control form of the SARS-CoV-2 spread dynamics model in minimizing the number of exposed populations by implementing testing and minimizing the infected population by implementing treatment. Optimal control analysis is carried out using the Pontryagin Maximum Principle, while numerical calculations for simulation use the Forward-Backward Runge-Kutta method with the help of MATLAB R2021a software. The results of the optimal control analysis conducted on 3 simulations with different vaccination values and incubation periods show that the application of both control strategies to the COVID-19 spread model in Indonesia is effective in reducing the number of infected individuals to 99.9%, but cannot maintain the population size.